THU0223 Impact of treatment in patients with rheumatoid arthritis and depressive symptoms in the monarch phase 3 trial of sarilumab. (12th June 2018) - Strand, V.; Hagino, O.; Guillonneau, S.; Boklage, S.; Reaney, M.; Sadeh, J.; Narcisse, N.; Mangan, E.; Kimura, T.
Abstract : Background: In the MONARCH Phase 3 randomised controlled trial (RCT) [NCT02332590 ], sarilumab subcutaneous (SC) 200 mg every 2 weeks (q2w) improved clinical outcomes and multiple aspects of health status/health-related quality of life (HRQoL), as measured by the Medical Outcomes Survey Short Form (SF-36) questionnaire, to levels greater than adalimumab SC 40 mg q2w. Both treatments were administered as monotherapy in patients with active rheumatoid arthritis (RA) who had discontinued treatment with methotrexate. Depression/mood disorder is a common co-morbidity in people with RA. Objectives: To explore whether observed differences in health status/HRQoL following treatment with sarilumab compared with adalimumab are also seen in the subgroup of patients in the MONARCH trial with probable depressive symptoms. Methods: Post-hoc statistical analyses were performed. Patients were categorised as having probable major depressive disorder 1 (PMDD; SF-36 mental health (MH) domain score ≤56) or probable depressed mood and anhedonia 2 (PDMA; score ≤10 on both items of the MH domain: "Have You Felt Downhearted and Depressed" and "Have You Felt So down in the Dumps that nothing could cheer you up"). Least squares mean (LSM) differences in changes from baseline (CFB) in SF-36 domains at Week 24 were calculated for sarilumab PMDD/PDMA versus adalimumab PMDD/PDMA. Sensitivity analysis included adjustment for Disease Activity Score 28 C-reactive protein (DAS28-CRP) at baseline. Results: Of the 369 patients from MONARCH, 250 (67.78%) were categorised with PMDD (mean age 52 years, 85% female) and 194 (52.6%) with PDMA (mean age 52 years, 87% female). Disease duration, DAS-28 CRP, tender and swollen joint counts (table 1) and SF-36 domain scores (figure 1) were similar between sarilumab and adalimumab within the PMDD and PDMA subpopulations at baseline. LSM differences in CFB in SF-36 domains were greater for sarilumab versus adalimumab at Week 24 in physical functioning (PF), bodily pain (BP), vitality (VT) and social functioning (SF) domains in both the PMDD and PDMA subgroups, and role-physical (RP) in the PMDD subgroup (nominal p<0.05) (figure 1). Sensitivity analysis showed similar results. Conclusions: Among patients with RA and probable depressive symptoms, sarilumab SC 200 mg q2w monotherapy was more effective than adalimumab SC 40 mg q2w monotherapy in demonstrating clinically meaningful improvements in some domains of health status/HRQoL. This may be a function of the different target of sarilumab (soluble IL-6 receptor [sIL-6R]) and associated improvements in disease activity versus adalimumab (tumour necrosis factor [TNFα]). References: [1] Matcham, et al. BMC Musculoskeletal Disorders2016;17:224. [2] Sun Y, et al. EULAR Congress2017; June 14–172017; Madrid, Spain. Acknowledgements: Research sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, AstraZeneca, Bayer, Boehringer Ingelheim, Celltrion, Corrona, Crescendo Bioscience, Eli Lilly, Genentech/Roche, GlaxoSmithKline, Horizon, Janssen, Merck, Novartis, Pfizer, Regeneron Pharmaceuticals, Samsung, Sandoz, Sanofi and UCB, O. Hagino Shareholder of: Sanofi, Employee of: Sanofi, S. Guillonneau Shareholder of: Sanofi, Employee of: Sanofi, S. Boklage Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., M. Reaney Shareholder of: Sanofi, Employee of: Sanofi, J. Sadeh Shareholder of: Sanofi, Employee of: Sanofi, N. Narcisse Consultant for: Sanofi, E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., T. Kimura Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc.